Turkish translation, validation, and reliability analysis of pediatric eosinophilic esophagitis symptom severity module version 2.0 - Yılmaz, Özlem; Kızılkan Uslu, Nuray; Özgür, Taner; Güller, Dilek; Tümgör, Gökhan; Usta, Merve; Polat, Esra; Başarır Özkan, Tanju; Baysoy, Gökhan; Korkut Uğraş, Meltem; Baygül, Arzu; Saçkesen, Cansın; et al. (Wolters Kluwer Health, 2022)
The Paediatric Eosinophilic Esophagitis Symptom Severity Modules Version 2.0 (T-PEESv2.0) was developed in English as a valid, reliable questionnaire for follow up. This work aimed to develop a Turkish version of T-PEESv2.0 via translation and cultural adaptation and then to test its validation and reliability. Methods: The PEESv2.0 was translated into Turkish by standardized procedural steps completed in cooperation with the Mapi Research Trust. The final version of the questionnaire was submitted to eosinophilic oesophagitis patients or their parents at 2 times point separated by 1 week. An age-matched control group was used to test the discriminant validity. Construct validity was tested using the Wilcoxon test, and internal consistency was tested using Cronbach's alpha. Test-retest reliability was measured with Cohen's kappa and intraclass correlation coefficient. Results: One hundred twenty-eight participants (70 patients, 58 parents) were enrolled. Fifty-eight (39.1%) of them completed T-PEESv2.0-parent by proxy and 70 (54.7%) were T-PEESv2.0. The Cronbach's alpha coefficient and intraclass correlation coefficient for test-retest reliability were >0.70 for both questionnaires and for all domain (frequency and severity) and total scores. For discriminant validity analysis, subscale (frequency and domain) and total scores of the patient group were compared with those of the control group. The subscale and total scores were significantly different between the groups (P < 0.05). Conclusion: T-PEESv2.0 appeared to be valid and reliable, ready to be introduced as a clinical and research tool for the assessment of patients with eosinophilic oesophagitis.
Keywords: Children; Eosinophilic; Esophagitis; Validation; Reliability; Symptom